Dampak Integritas dan Dukungan Organisasi Terhadap Kinerja Pegawai - Sudung Simatupang; Desi Susanti; Marto Silalahi; Ernest Grace; Efendi Efendi (Universitas Batanghari, 2023)
The reform of civil servant bureaucracy today is expected to be able to produce good civil servant performance in supporting a good public service system to the community. The implementation of integrity as a moral value and honesty in carrying out the work of civil servants can support their performance and organizational support is expected to always be given to employees so that the ability to manage their performance can be achieved. The purpose of this research is to determine the influence of organizational integrity and support on employee performance at the Suka Mbayak Village Head Office located in Suka Mbayak Village, Karo Regency with a total of 37 employees. By using SPSS, the results of the study found the direction coefficient of multiple regression found a positive direction of integrity and organizational support for employee performance. The hypothetical results found a positive and significant influence of integrity on employee performance and a positive and significant influence of organizational support on employee performance. With the high integrity of employees and good organizational support for employees, it will directly or indirectly produce good performance as well.